The Influence of Compensation and Job Stress on Turnover Intention in the Sales Division of PT. Astra International Tbk – TSO Auto2000 Tebet Saharjo - Millenigita, Anggun Ashyfa Rizqi; Permatasari, Rita Intan; AlMunir, Sipon (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2023)
Turnover Intentioncharacterized by various things related to employee behavior which is reflected in the provision of compensation and work stress. This research aims to determine the effect of compensation and work stress on turnover intention in the sales division of PT. Astra International Tbk – TSO Auto2000 Tebet Saharjo. This research uses a causal associative approach with a survey method using the SPSS version 25 application. The population is 55 people and the sample is 33 people based on a purposive sampling technique. Data were collected using a questionnaire with a Likert scale of 1 to 5. The results showed that: compensation partially had a negative and significant effect on employee turnover intention, work stress partially had a positive and significant effect on employee turnover intention, compensation and work stress simultaneously had a significant effect on turnover intention of PT Sales Division Employees. Astra International Tbk – TSO Auto2000 Tebet Saharjo. The contribution of compensation and work stress was 41.2%, the remaining 58.8% was influenced by other variables not examined in this research.